The Effect of Cognitive Commitment of Behavioral Therapy on Internet Addiction among Adolescents in Kupang City - Antonia Helena Hamu; Ah. Yusuf; Yuni A. Sufyanti; Hendy M. Margono; Triyana PD; Abdul Fauzi (International Journal of Nursing and Health Services (IJNHS), 2020)
Internet used increased rapidly among adolescent. It was due an addiction since assessible of internet was very easy. A quasiexperimental study pre-test and post-test design was applied in this study. Fifty-eight samples were recruited and divided into experimental group (n=280) and the control group (n=30) by using the simple random sampling. We analyse all data with Wilcoxon Sign Ranks Test and Man-Whitney U Test and with a significance level was 0.05. The findings showed that there are positive effects cognitive commitment behavioral therapy on internet addiction among intervention group before and after receiving the intervention (p = 0,000). Regarding the mean difference, between the experimental and control group showed there are significant different on addiction (p = 0,000) after receiving the program. CCBT has a positive effect on lowering the level of internet addiction. Thefore, we recommended to apply CCBT effectively in the healh care services, school, as well as community community level to reduce internet addiction.